University Physics with Modern Physics - Wolfgang Bauer (McGraWHill, 2014)
Bauer & Westfall’s University Physics with Modern Physics,second edition, teaches students the fundamentals of physics through interesting, timely examples, a logical and consistent approach to problem solving, and an outstanding suite of online tools and exercises. Bauer & Westfall, University Physics with Modern Physics, second edition, weaves exciting, contemporary physics throughout the text with coverage of the most recent research by the authors and others in areas such as energy, medicine, and the environment. These contemporary topics are explained in a way that your students will find real, interesting, and motivating.Bauer & Westfall’s University Physics with Modern Physics is designed for the calculus-based introductory physics course and is well suited for students in Physics, Engineering, and the Life and Physical Sciences. The text acknowledges the latest advances in physics education with a traditional table of contents.